Market Orientation, Learning Orientation and SMES Performance: The Mediating Role of Innovation - Haryanto, Aris Tri; Haryono, Tulus; Sawitri, Hunik Sri Runing (International Review of Management and Marketing, 2017)
This study aims to empirically demonstrate the relationship of market orientation, learning orientation on innovation and business performance within the scope of the small and medium enterprises (SMEs). Besides, this research also explaines the importance of company's innovation as a mediating relation to improve business performance. The samples of this study were 155 managers or owners of Meubeller SMEs in the Region of Karisidenan Surakarta. The sampling technique used in this research was purposive sampling. The basic consideration of this research was the experience of the SMEs Meubeller (either the manager or owner) in managing their businesses. The hypothesis testing results showed that market orientation gave positive effect on business performance and innovation of the company. Orientation learning gave positive effect on business performance and innovation of the company. Company's innovation influenced business performance. Keyword: Market Orientation, Learning Orientation, Performance, Innovation JEL Classifications: L1, M31